1999
DOI: 10.1152/jappl.1999.86.3.840
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of muscle relaxation time after creatine loading

Abstract: The effect of creatine (Cr) supplementation on muscle isometric torque generation and relaxation was investigated in healthy male volunteers. Maximal torque (Tmax), contraction time (CT) from 0.25 to 0.75 of Tmax, and relaxation time (RT) from 0.75 to 0.25 of Tmax were measured during 12 maximal isometric 3-s elbow flexions interspersed by 10-s rest intervals. Between the pretest and the posttest, subjects ingested Cr monohydrate (4 x 5 g/day; n = 8) or placebo (n = 8) for 5 days. Pretest Tmax, CT, and RT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
52
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 31 publications
(66 reference statements)
9
52
0
2
Order By: Relevance
“…Since the relaxation process accounts for an important fraction of total energy consumption (Bergstrom & Hultman, 1988) during repeated muscle contraction there might be a performance benefit if relaxation time were decreased. Van Leemputte et al (1999) suggested that the mechanism facilitating relaxation was the rise in PCr concentration which enabled the sarcoplasmic Ca¥-ATPase to operate at a higher thermodynamic efficiency or at a higher rate of cross-bridge detachment (van Leemputte et al 1999). Changes in EMG in response to Cr supplementation have not been assessed extensively and comparisons between studies are difficult since different techniques have been employed.…”
Section: Fatiguementioning
confidence: 99%
See 4 more Smart Citations
“…Since the relaxation process accounts for an important fraction of total energy consumption (Bergstrom & Hultman, 1988) during repeated muscle contraction there might be a performance benefit if relaxation time were decreased. Van Leemputte et al (1999) suggested that the mechanism facilitating relaxation was the rise in PCr concentration which enabled the sarcoplasmic Ca¥-ATPase to operate at a higher thermodynamic efficiency or at a higher rate of cross-bridge detachment (van Leemputte et al 1999). Changes in EMG in response to Cr supplementation have not been assessed extensively and comparisons between studies are difficult since different techniques have been employed.…”
Section: Fatiguementioning
confidence: 99%
“…Indeed, it has been shown that following Cr supplementation in rats, twitch and tetanic half-relaxation times (HRT) are decreased (Wakatsuki et al 1994). In human elbow flexors relaxation time of voluntary contractions is also less (van Leemputte et al 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations